Demo Pastry Untuk Menciptakan Inovasi Ide Jualan Umkm di Kampung Bekelir Tangerang - Triandi Pradana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Bekelir village which was originally a slum village has now turned into an independent village. Starting from self-help of the village community to have a comfortable place to live, so a colorful village concept was created that can be seen today. The local government service, through the Environmental Service, gave permission to the village community through Pak Kholik as the head of the RW to sell on the banks of the Cisadane river. Due to information from the inhabitant of Bekelir Village where they were constrained by the idea of UMKM. UMKM Opportunity are given at a very low cost, namely Rp. 5000/Day will be profitable for inhabitant who will sell the produk. Therefore, this community service is carried out to provide the knowledge needed by the inhabitant of Bekelir Village. The training provided is how to make Putu Ayu Cake starting from the Mise en place process, the recipe used, the method used, the equipment needed and quality results. In addition, in this training, residents also received material on how to calculate production costs, determine selling prices and the profits to be obtained. It is hoped that this Community service will have a direct impact on improving the local economy.